Contemporary Iraqi arts techniques and their reflection on the products of the students of Art Education (Al-Academy, 2023)
The techniques of contemporary Iraqi painting and their reflection on the productions of students of art education is an important subject in the field of painting at the theoretical and practical levels in academic study, whether theoretical or practical. Al-Iraqi is one of the arts with historical roots and a distinguished position among other artistic genres. Painting has received a sufficient level of development through the use of various contemporary techniques to advance it for the better.The methodological framework included the problem of research and the need for it, and then the importance of research came in shedding light on the techniques of contemporary Iraqi painting, and the impact of these techniques on the productions of students of art education and the benefit that was reflected in their official productions. The research aimed to reveal the immediate techniques and their mechanisms, and the extent of their reflection on the productions of art education students. By stopping and defining terms?The theoretical framework included two sections: the first: a historical introduction to contemporary Iraqi painting, its roots and beginnings. The second: contemporary Iraqi painting techniques. The research procedures included: The research community and the research sample included (3) official works,The results and conclusions reached by the two researchers:1. The techniques appeared strongly in all the art education students’ outputs in all samples.2. The student relied on his imagination to produce new formal compositions.3. The small number of textbooks on drawing techniques to be taught to students of the Department of Art Education.